2001
DOI: 10.1097/00003246-200111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Liver and intestinal lactate metabolism in patients with acute hepatic failure undergoing liver transplantation

Abstract: The liver is a net producer of lactate in patients with ALF and an elevated whole blood lactate. After liver transplantation, the graft becomes a consumer of lactate as shown by the negative lactate gradient. The degree of consumption is dependent on portal venous lactate concentration and cold ischemic time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 36 publications
1
59
0
2
Order By: Relevance
“…The measurements of lactate concentration are considered to be one of the most reliable biochemical parameters to determine the severity and outcome of acute liver failure and reflect the severity of liver injury (33). Hyperlactatemia develops under clinical conditions in approximately 80% of patients suffering from fulminant liver failure, for example, due to hepatitis-induced enhancement of hepatic and extrahepatic anaerobic glycolytic activity with higher lactate generation together with a reduced hepatocyte capacity and function to clear lactate, altogether resulting in a net hepatic lactate production (34,35). In control, the hepatocellular integrity in the absence of Con A (sham) was not affected by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of lactate concentration are considered to be one of the most reliable biochemical parameters to determine the severity and outcome of acute liver failure and reflect the severity of liver injury (33). Hyperlactatemia develops under clinical conditions in approximately 80% of patients suffering from fulminant liver failure, for example, due to hepatitis-induced enhancement of hepatic and extrahepatic anaerobic glycolytic activity with higher lactate generation together with a reduced hepatocyte capacity and function to clear lactate, altogether resulting in a net hepatic lactate production (34,35). In control, the hepatocellular integrity in the absence of Con A (sham) was not affected by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia may contribute to raised ICP because increased glucose influx leads to cerebral lactic acid accumulation. 71 Hence it may be prudent to keep blood glucose within the normal limits.…”
Section: Nutritional and Metabolic Supportmentioning
confidence: 99%
“…indicated by slightly abnormal coagulation tests and elevated transaminase levels). It has been shown that patients with acute liver failure actually have a splanchnic release of lactate [8], thought to be due to accelerated splanchnic glycolysis and defects in hepatic pyruvate metabolism [9]. In healthy individuals, hepatic lactate clearance is estimated to be up to 70% of the whole body clearance.…”
Section: Discussionmentioning
confidence: 99%